Development and Validation Innovation of Self-Control, FOMO, and Phubbing Scales for High School Students: A Psychometric Approach with Structural Factor Analysis - Moch. Affan Shafry Bukhori; Agus Tinus; Beti Istanti Suwandayani (Universitas PGRI Yogyakarta, 2026)
This study developed and validated the Self-Control, FOMO, and Phubbing scales for high school students using a psychometric approach. Content validity was assessed through Aiken's V, which showed a CVR greater than 0.78, while empirical validity testing identified 44 of 56 items as valid. The reliability test yielded a Cronbach's Alpha of 0.90 (highly reliable), and the data met the assumptions of normality (Shapiro–Wilk: Self-Control, p = 0.437; FOMO, p = 0.257; Phubbing, p = 0.123) and homogeneity (Levene's, p = 0.221). EFA analysis yielded a KMO of 0.654, with five factors explaining 70.20% of the variance. CFA produced a model fit that was close to good (CFI = 0.851; TLI = 0.826; RMSEA = 0.0961; SRMR = 0.0918). The study's results concluded that this scale is valid, reliable, and capable of accurately measuring phubbing tendencies. The findings confirm that self-control plays a crucial mediating role in reducing FOMO-induced phubbing. The novelty of this study lies in the development of an instrument that has been comprehensively validated and culturally adapted for the Indonesian adolescent context, unlike previous studies that only adapted foreign scales without thorough validity testing. This scale can be used as a diagnostic tool and a basis for preventive interventions to enhance digital literacy and mitigate the negative effects of excessive digital engagement on adolescents. Keywords: adolescents, FOMO, phubbing, psychometrics, self-control